At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Sure, let's solve the given expression step-by-step:
The expression we need to evaluate is:
[tex]\[ \frac{\frac{n!}{r!(n-r)!}}{1-25-26-31-6s-2} \][/tex]
### Step 1: Calculate [tex]\( n! \)[/tex]
Given [tex]\( n = 5 \)[/tex]:
[tex]\[ n! = 5! = 5 \times 4 \times 3 \times 2 \times 1 = 120 \][/tex]
### Step 2: Calculate [tex]\( r! \)[/tex]
Given [tex]\( r = 3 \)[/tex]:
[tex]\[ r! = 3! = 3 \times 2 \times 1 = 6 \][/tex]
### Step 3: Calculate [tex]\( (n - r)! \)[/tex]
Given [tex]\( n = 5 \)[/tex] and [tex]\( r = 3 \)[/tex]:
[tex]\[ (n - r)! = (5 - 3)! = 2! = 2 \times 1 = 2 \][/tex]
### Step 4: Calculate the numerator [tex]\( \frac{n!}{r!(n-r)!} \)[/tex]
Now, substitute the values into the numerator formula:
[tex]\[ \frac{n!}{r!(n-r)!} = \frac{120}{6 \times 2} = \frac{120}{12} = 10 \][/tex]
### Step 5: Calculate the denominator [tex]\( 1 - 25 - 26 - 31 - 6s - 2 \)[/tex]
Given [tex]\( s = 2 \)[/tex]:
[tex]\[ 1 - 25 - 26 - 31 - 6s - 2 = 1 - 25 - 26 - 31 - 6 \times 2 - 2 = 1 - 25 - 26 - 31 - 12 - 2 = 1 - 96 = -95 \][/tex]
### Step 6: Calculate the final result
Now we have the numerator value [tex]\( 10 \)[/tex] and the denominator value [tex]\( -95 \)[/tex]:
[tex]\[ \frac{10}{-95} = -\frac{10}{95} = -\frac{2}{19} \approx -0.10526315789473684 \][/tex]
So, the final detailed step-by-step result of the expression is approximately:
[tex]\[ -0.10526315789473684 \][/tex]
The expression we need to evaluate is:
[tex]\[ \frac{\frac{n!}{r!(n-r)!}}{1-25-26-31-6s-2} \][/tex]
### Step 1: Calculate [tex]\( n! \)[/tex]
Given [tex]\( n = 5 \)[/tex]:
[tex]\[ n! = 5! = 5 \times 4 \times 3 \times 2 \times 1 = 120 \][/tex]
### Step 2: Calculate [tex]\( r! \)[/tex]
Given [tex]\( r = 3 \)[/tex]:
[tex]\[ r! = 3! = 3 \times 2 \times 1 = 6 \][/tex]
### Step 3: Calculate [tex]\( (n - r)! \)[/tex]
Given [tex]\( n = 5 \)[/tex] and [tex]\( r = 3 \)[/tex]:
[tex]\[ (n - r)! = (5 - 3)! = 2! = 2 \times 1 = 2 \][/tex]
### Step 4: Calculate the numerator [tex]\( \frac{n!}{r!(n-r)!} \)[/tex]
Now, substitute the values into the numerator formula:
[tex]\[ \frac{n!}{r!(n-r)!} = \frac{120}{6 \times 2} = \frac{120}{12} = 10 \][/tex]
### Step 5: Calculate the denominator [tex]\( 1 - 25 - 26 - 31 - 6s - 2 \)[/tex]
Given [tex]\( s = 2 \)[/tex]:
[tex]\[ 1 - 25 - 26 - 31 - 6s - 2 = 1 - 25 - 26 - 31 - 6 \times 2 - 2 = 1 - 25 - 26 - 31 - 12 - 2 = 1 - 96 = -95 \][/tex]
### Step 6: Calculate the final result
Now we have the numerator value [tex]\( 10 \)[/tex] and the denominator value [tex]\( -95 \)[/tex]:
[tex]\[ \frac{10}{-95} = -\frac{10}{95} = -\frac{2}{19} \approx -0.10526315789473684 \][/tex]
So, the final detailed step-by-step result of the expression is approximately:
[tex]\[ -0.10526315789473684 \][/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.